Ethyl alcohol supplement not beneficial to cattle in feedlot tests - W Garrett; J Meyer (California Agriculture, 1963)
This trial was conducted to evaluate observations by a supplier of industrial alcohol indicating the possibility of a beneficial production response when feedlot cattle were given small amounts of ethanol in their water. The experiment was conducted for a 105-day period from July through October in 1962. Four pens of three Hereford steers received an identical ration with two pens (six steers) receiving alcohol in the water at a concentration providing 8 oz. of denatured ethanol per head daily. Dispensing apparatus was a 100-gallon tank supplied with a float valve and a small, 8 × 8 × 2-inch drinking pan to minimize evaporation. Water and the ethanol were added to the tank daily. Similar drinkers used in control pens were equipped with water meters to record water consumption.